Blast Liquefaction Test of Saturated Sand Foundations Disposed by a Drainage Rigid Pile - Songtao Ni; Yumin Chen; Runze Chen; Hanlong Liu; Changchun Li; Shaobin Hu (Shock and Vibration)
Drainage rigid piles represent a commonly used antiliquefaction treatment for saturated sand foundations. Small-scale model tests on the liquefaction-resistant characteristics of drainage rigid piles subjected to blasting were conducted in this study. The effect of ordinary rigid piles and drainage rigid piles on the disposal of saturated sand foundations was investigated by using carbon dioxide (CO2) fracturing to generate explosive vibratory loads. The test results showed that the blast vibration load increased the relative density of the site by approximately 10% and that the relative density was proportional to the burial depth. The site vertical acceleration attenuations resulting from the two blasts were 35% and 45%, respectively, and the variation pattern of vertical acceleration on both sides of drainage rigid piles and ordinary piles is similar. Drainage rigid piles can dissipate more than 70% of the excess pore water pressure under liquefaction and can quickly accumulate excess pore water pressure and, likewise, quickly dissipate excess pore water pressure. The higher the excess pore water pressure at a site is, the more effective the disposal by a drainage rigid pile is. This field test provides a design reference for the engineering application of drainage rigid piles.